EVALUASI PROFITABILITAS PROYEK SARFAS TUKS MIGAS TANJUNG SEKONG PT WIJAYA KARYA TAHUN 2017-2019 - Aswanta Wisnu Pradhana; Suyatmin Waskito Adi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to evaluate the profitability of the Tanjung Sekong oil and gas infrastructure project at PT Wijaya Karya in 2017–2019. The data was collected from the Tanjung Sekong Oil and Gas Infrastructure project report in 2017-2019. This research used NPV, IRR, profitability index, payback period, ROE, and ROI to conduct it. The result shows that the NPV obtained is positive, IRR > interest rate, Profitability Index > 1, the payback period for the project from 2017-2019 is returned within 1 year, 11 months and 5 days, the ROE value obtained is 13.15% and the ROI value of 18.18%. The project is feasible to continue and is feasible to be an investment project.